Transcutaneous electrical nerve stimulation for balance and gait rehabilitation in stroke survivors: A systematic review and Meta-analysis - Alashram, Anas R (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2025)
Balance and impairments are common consequences of stroke. For decades, transcutaneous electrical nerve stimulation (TENS) has been used in stroke rehabilitation. This review aims to explore the effects of TENS on balance and gait deficits in stroke survivors and to identify its contraindications.“PubMed, Scopus, PEDro, CINAHL, EMBASE, and Web of Science” were searched until February 2025. Randomized trials included stroke survivors, administrated TENS, compared with rest or active interventions, and included scales that assessed gait or balance abilities. The PEDro scale was used to determine the quality of the included studies. Comprehensive Meta-Analysis Version 4 was used for meta-analysis.Ten studies met the inclusion criteria. In total, 465 patients with stroke (mean age 58.84 years; 65% male) were involved in this review. The included studies' PEDro scale scores ranged from 6 to 9, with a median of 8. The meta-analysis showed a potential effect of TENS on the Timed Up and Go (TUG) test (SMD: 0.458, 95% CI: –0.116 to 1.031, p=0.118, I²=75%), but the results were inconclusive due to lack of statistical significance and high heterogeneity. For gait, the meta-analysis showed a significant positive effect of TENS on the 10-Meter Walk Test (SMD=0.831, 95% CI: 0.448 to 1.214, p<0.001; I²=0%).TENS may improve gait, but its effect on balance remains inconclusive. It is contraindicated in stroke patients with heart pacemakers, skin issues at the electrode site, severe cognitive impairments, sensory deficits, pregnancy, psychotic disorders, uncontrolled hypertension or diabetes, seizures, and severe heart or lung disease. Further studies are recommended.
Keywords: Transcutaneous Electrical Nerve Stimulation; Stroke; Gait; Balance; Rehabilitation